Altered β1-3-adrenoceptor influence on α2-adrenoceptor-mediated control of catecholamine release and vascular tension in hypertensive rats - Berg, Torill (Frontiers in Physiology, 2015)
α2- and β-adrenoceptors (AR) reciprocally control catecholamine release and vascular tension. Disorders in these functions are present in spontaneously hypertensive rats (SHR). The present study tested if α2AR dysfunctions resulted from altered α2AR/βAR interaction. Blood pressure was recorded through a femoral artery catheter and cardiac output by an ascending aorta flow probe. Total peripheral vascular resistance (TPR) was calculated. Norepinephrine release was stimulated by a 15-min tyramine-infusion, which allows presynaptic release-control to be reflected as differences in overflow to plasma. Surgical stress activated some secretion of epinephrine. L-659,066 (α2AR-antagonist) enhanced norepinephrine overflow in normotensive controls (WKY) but not SHR. Nadolol (β1+2) and ICI-118551 (β2), but not atenolol (β1) or SR59230A (β(3)/1L) prevented this increase. All βAR antagonists allowed L-659,066 to augment tyramine-induced norepinephrine overflow in SHR and epinephrine secretion in both strains. Inhibition of cAMP-degradation with milrinone and β3AR agonist (BRL37344) enhanced the effect of L-659,066 on release of both catecholamines in SHR and epinephrine in WKY. β1/2AR antagonists and BRL37344 opposed the L-659,066-dependent elimination of the TPR-response to tyramine in WKY. α2AR/βAR antagonists had little influence on the TPR-response in SHR. Milrinone potentiated the L-659,066-dependent reduction of the TPR-response to tyramine. Conclusions: β2AR activity was a required substrate for α2AR auto inhibition of norepinephrine release in WKY. β1+2AR opposed α2AR inhibition of norepinephrine release in SHR and epinephrine secretion in both strains. βAR-α2AR reciprocal control of vascular tension was absent in SHR. Selective agonist provoked β3AR-Gi signaling and influenced the tyramine-induced TPR-response in WKY and catecholamine release in SHR.